Mining the Aegilops tauschii gene pool: evaluation, introgression and molecular characterization of adult plant resistance to leaf rust and seedling resistance to tan spot in synthetic hexaploid wheat - Kalia, Bhanu (Kansas State University, 2015)
Leaf rust, caused by fungus Puccinia triticina, is an important foliar disease of wheat worldwide. Breeding for race-nonspecific resistant cultivars is the best strategy to combat this disease. Aegilops tauschii, D genome donor of hexaploid wheat, has provided resistance to several pests and pathogens of wheat. To identify potentially new adult plant resistance (APR) genes, 371 geographically diverse Ae. tauschii accessions were evaluated in field with leaf rust (LR) composite culture of predominant races. Accessions from Afghanistan only displayed APR whereas both seedling resistance and APR were common in the Caspian Sea region. Seventeen accessions with high APR were selected for production of synthetic hexaploid wheat (SHW), using ‘TetraPrelude’ and/or ‘TetraThatcher’ as tetraploid parents. Six SHWs were produced and evaluated for APR to LR and resistance to tan spot at seedling stage. Genetic analysis and mapping of APR introgressed from accession TA2474 was investigated in recombinant inbred lines (RIL) population derived from cross between SHW, TA4161-L3 and spring wheat cultivar, ‘WL711’. Genotyping-by-sequencing approach was used to genotype the RILs. Maximum disease severity (MDS) for LR was significantly correlated among all experiments and APR to LR was highly heritable trait in this population. Nine genomic regions significantly associated with APR to LR were QLr.ksu-1AL, QLr.ksu-1BS, QLr.ksu-1BL.1, QLr.ksu-1BL.2, QLr.ksu-2DS, QLr.ksu-2DL, QLr.ksu-5AL, QLr.ksu-5DL and QLr.ksu-6BL. Association of QLr.ksu-1BL.1 with marker Xwmc44 indicated this locus could be slow-rusting APR gene, Lr46/Yr29. QTLs detected on 2DS, 2DL and 5DL were contributed by TA4161-L3 and are novel, along with QLr.ksu-5AL. Tan spot, caused by necrotrophic fungus, Pyrenophora tritici-repentis, has recently emerged as a damaging disease of wheat worldwide. To identify QTLs associated with resistance to Race 1 of P. tritici-repentis, F[subscript]2:3 population derived from cross between SHW, TA4161-L1 and winter wheat cultivar, ‘TAM105’ was used. Two major effect QTLs, QTs.ksu-1AS.1 and QTs.ksu-7AS were significantly associated with tan spot resistance and contributed by TA4161-L1. QTs.ksu-7AS is a novel QTL and explained 17% of the phenotypic variation. Novel QTLs for APR to LR and tan spot identified in SHWs add new variation for broadening the gene pool of wheat and providing resources for breeding of durable resistant cultivars.
Keywords: Aegilops tauschii; Adult Plant Resistance; Synthetic hexaploid wheat; Leaf Rust; QTL mapping; Tan spot; Wheat; Genetics (0369); Plant Pathology (0480)